2014
DOI: 10.2337/dc13-2329
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Persistent Organic Pollutants: Relationship With Abnormal Glucose Metabolism and Visceral Adiposity

Abstract: OBJECTIVE The contribution of persistent organic pollutants (POPs) to the pandemic of type 2 diabetes mellitus and obesity has been assumed but remains speculative. Our study aimed at investigating the relationship of POP levels with detailed markers of glucose metabolism and body composition. RESEARCH DESIGN AND METHODS Glucose tolerance was determined in a group of normal-weight and obese individuals. Fat distribution was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 39 publications
1
55
0
Order By: Relevance
“…Therefore, DDE has consistently been positively associated with BMI (230) (224) (107) (104) (218) (128) (164) (312) (343), waist circumference (223) (107) (226), and visceral and subcutaneous adipose tissue (107). Only two studies found sex differences in the relationship between DDE exposure and obesity.…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, DDE has consistently been positively associated with BMI (230) (224) (107) (104) (218) (128) (164) (312) (343), waist circumference (223) (107) (226), and visceral and subcutaneous adipose tissue (107). Only two studies found sex differences in the relationship between DDE exposure and obesity.…”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
“…When PCBs were grouped together, positive associations were found with an increased risk of becoming obese (108), BMI (218), and waist circumference (223). Furthermore, in a study of obese adults without diabetes, adipose levels of PCBs were positively associated with weight, BMI, waist circumference, and visceral adipose tissue (107). …”
Section: Associations Between Pop Exposures and The Development Of Obmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that besides the imbalance of energy intake and expenditure, other genetic, behavioral and environmental factors may contribute to the development of obesity [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Humans are predominantly exposed through the consumption of contaminated food, mainly meat, fish, and dairy products [1], in agriculture for crop protection, in homes for controlling any pest and gardens for destroying unwanted species of plants [2]. Because of their ability to resist environmental degradation, these substances are omnipresent in food products, and found all around the world, even in areas where they have never been used like Antarctica [3,4].…”
Section: Introductionmentioning
confidence: 99%